1997
DOI: 10.1097/00000374-199708000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use Disorders, Consumption Patterns, and Health-Related Quality of Life of Primary Care Patients

Abstract: This study examined the association of alcohol use disorders and consumption patterns with various dimensions of Health-Related Quality of Life (HRQOL) in primary care patients, as measured by the SF-36 Health Survey. A probability sample of 1333 primary care patients completed the Alcohol Use Disorder and Associated Disabilities Interview Schedule to determine the presence of alcohol abuse or dependence disorders, and answered questions about patterns of alcohol consumption. Physical and Mental Health Compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
0
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 0 publications
6
61
0
4
Order By: Relevance
“…This may be the case in the COMBINE Study because, at baseline, most individuals were drinking frequently (on average, 75% of the days) but were distinguished by the high levels of consumption, which reached an average of 12.5 DDD. Volk et al (1997) similarly found, in a sample of primary care patients, that heavy episodic drinkers and those who had frequent heavy drinking reported lower scores on the SF-36 mental health and role functioning domains. They also found that those diagnosed with alcohol dependence reported lower quality-of-life scores, but this was not the case for those diagnosed with alcohol abuse.…”
Section: Correlations Between Drinking and Secondary Variables By Timmentioning
confidence: 78%
See 1 more Smart Citation
“…This may be the case in the COMBINE Study because, at baseline, most individuals were drinking frequently (on average, 75% of the days) but were distinguished by the high levels of consumption, which reached an average of 12.5 DDD. Volk et al (1997) similarly found, in a sample of primary care patients, that heavy episodic drinkers and those who had frequent heavy drinking reported lower scores on the SF-36 mental health and role functioning domains. They also found that those diagnosed with alcohol dependence reported lower quality-of-life scores, but this was not the case for those diagnosed with alcohol abuse.…”
Section: Correlations Between Drinking and Secondary Variables By Timmentioning
confidence: 78%
“…In general, alcohol-dependent patients have lower quality-of-life scores as compared with the norms of the general population (Daeppen et al, 1998;Morgan et al, 2003) and with other medical patients (Foster et al, 1997;Volk et al, 1997). In addition, higher severity of alcohol dependence is predictive of lower quality of life for alcoholics at the beginning of treatment (Morgan et al, 2004).…”
mentioning
confidence: 99%
“…Payá et al (2002), em estudo com indivíduos do sexo masculino dependentes de álcool, observaram uma qualidade de vida mediana, considerando-se as médias e os valores preconizados para o melhor padrão de qualidade de vida. Volk et al (1997) também constataram que pacientes dependentes do álcool apresentam piores escores de qualidade de vida. Já Wilson, Parsons e Wakefield (1999), conduziram um estudo sobre o tabaco, o qual demonstrou prejuízos em todas as dimensões do SF-36 entre os tabagistas moderados e graves.…”
Section: Discussionunclassified
“…However, it is possible to quote studies by Volk, Steinbauer, and Cass (1997) and Daeppen, Krieg, Burnand, and Yersin (1998), in which it has been confirmed that dependent persons are characterized by a significantly lower life quality as compared to the general population and to persons suffering from other chronic diseases. Also an analysis of publications from the years 1993-2004, made by Donovan, Mattson, Cisler, Longabaugh, and Zweben (2005), indicates a clearly lowered level of life quality in the alcohol-addicted persons.…”
Section: Discussionmentioning
confidence: 99%